Partitioning of fungal assemblages across different marine habitats. Issue 2 (16th February 2016) - Jeffries, Thomas Charles; Curlevski, Nathalie J.; Brown, Mark Vincent; Harrison, Daniel P.; Doblin, Martina A.; Petrou, Katherina; Ralph, Peter J.; Seymour, Justin R.
Summary: Fungi are a highly diverse group of microbes that fundamentally influence the biogeochemistry of the biosphere, but we currently know little about the diversity and distribution of fungi in aquatic habitats. Here we describe shifts in marine fungal community composition across different marine habitats, using targeted pyrosequencing of the fungal Internal Transcribed Spacer (ITS) region. Our results demonstrate strong partitioning of fungal community composition between estuarine, coastal and oceanic samples, with each habitat hosting discrete communities that are controlled by patterns in salinity, temperature, oxygen and nutrients. Whereas estuarine habitats comprised a significant proportion of fungal groups often found in terrestrial habitats, the open ocean sites were dominated by previously unidentified groups. The patterns observed here indicate that fungi are potentially a significant, although largely overlooked, feature of the ocean's microbiota, but greater efforts to characterize marine species are required before the full ecological and biogeochemical importance of marine fungi can be ascertained.